Isotope effect in turbulent transport in high density FT-2 tokamak discharges. (1st June 2022) - Kouprienko, D.V.; Gurchenko, A.D.; Gusakov, E.Z.; Altukhov, A.B.; Askinazi, L.G.; Belokurov, A.A.; Dyachenko, V.V.; Esipov, L.A.; Ivanov, V.A.; Kaledina, O.A.; Lashkul, S.I.; Shatalin, S.V.; et al.
Abstract: A detailed study of the general transport properties of the FT-2 tokamak shows significant isotopic difference in ohmically heated quasi-stationary plasma in high density regimes 〈 n e 〉 ≈ (6–9) × 10 19  m −3 . For deuterium, the signatures of a transition to the H-mode are found at a plasma density exceeding a certain value, while hydrogen plasma remains in L-mode in all comparable discharge scenarios. The origin of this isotopic discrepancy is studied both with energy transport analysis and direct turbulence and plasma velocity measurements performed with Langmuir probes and microwave diagnostics. A special, more complicated dynamic experimental series with current ramp up, performed in these high density regimes, demonstrated the stability and robustness of an improved energy confinement in deuterium, whereas a comparable confinement improvement in hydrogen plasma was observed.